Melodic figuration critical review and defiguration analytical methodology based on layers (2013)
The advanced project on the subject mentioned in the title concluded in the formulation of a methodology of the detailed analysis of the modal and tonal melody as a figuration, based on the following hypothetical premise, corroborated later by the experimentation carried out during the process and collection in an anthology of analyzed examples: an analytical method of figuration can be found without the problems of the current one. The focus was on cellular motifs or musical words, each of whose structures are built around a nuclear sound, root or lexeme and some previous or subsequent satellite sounds or morphemes, subordinated to it according to a figuration or functional arrangement by levels or orders, in such a way that figures of a given order function as derived nuclear around which satellite sounds of the subsequent order or level can be found.